Impact of the COVID-19 Pandemic on Solid Organ Transplant and Rejection Episodes in Brazil’s Unified Healthcare System - de Andrade, Luis Gustavo Modelli [UNESP]; Barbosa, Abner Macola Pacheco [UNESP]; da Rocha, Naila Camila [UNESP]; Cardoso, Marilia Mastrocolla de Almeida [UNESP]; Almeida, Juliana Tereza Coneglian de [UNESP]; Rugolo, Juliana Machado; Arantes, Lucas Frederico; Pontes, Daniela Ferreira Salomão [UNESP]; Ferreira, Gustavo Fernandes (MDPI, 2022)
Background: Brazil has the world’s largest public organ transplant program, which was severely affected by the COVID-19 pandemic. The primary aim of the study was to evaluate differences in solid organ transplants and rejection episodes during the COVID-19 pandemic compared to the five years before the pandemic in the country. Methods: A seven-year database was built by downloading data from the DATASUS server. The pandemic period was defined as March 2020 to December 2021. The pre-pandemic period was from January 2015 to March 2020. Results: During the pandemic, the number of solid organ transplants decreased by 19.3% in 2020 and 22.6% in 2021 compared to 2019. We found a decrease for each evaluated organ, which was more pronounced for lung, pancreas, and kidney transplants. The seasonal plot of rejection data indicated a high rejection rate between 2018 and 2021. There was also an 18% (IRR 1.18 (95% CI 1.01 to 1.37), p = 0.04) increase in the rejection rate during the COVID-19 pandemic. Conclusions: The total number of organ transplants performed in 2021 represents a setback of six years. Transplant procedures were concentrated in the Southeast region of the country, and a higher proportion of rejections occurred during the pandemic. Together, these findings could have an impact on transplant procedures and outcomes in Brazil.
Keywords: Brazil; COVID-19; graft rejection; organ transplant